Konseptualisasi Cara Pandang Islamisasi Bahasa - Moh. Ismail; Lisa Ihdiatul Jannah; Sujiat Zubaidi Saleh; Devi Rafika Sari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Similar terms are frequently heard in several languages, yet every language has its unique viewpoint. As a result, conceptual and semantic shifts within a language are frequent. Nevertheless, problems occur when these modifications are made to important Islamic jargon. It is well recognized that Islam and Arabic are closely related. The Qur'anic text is written in Arabic, which offers a strong basis for the language's semantic perpetuity. The purpose of this study is to investigate how stable the Arabic-Islamic language is and how meaning changes affect important terms in Islam. The research method used is library research, with data collection techniques involving the examination of books as primary sources and journals and articles related to the research topic as secondary sources. The results of the study suggest that certain languages that share terminology with important terms in Islam but have different meanings should be Islamized. The goal of language Islamization is to adapt Western viewpoints of a language to those of Islam, particularly with regard to upholding Islamic ideas. Although Arabic and other languages share many phrases, it is imperative to maintain the Islamic ideals and continuity of meaning in the vocabulary used.